2021
DOI: 10.1080/15592294.2021.1982158
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of accessible chromatin in quiescent cardiac fibroblasts and cardiac fibroblasts activated after myocardial infarction

Abstract: After myocardial infarction, the massive death of cardiomyocytes leads to cardiac fibroblast proliferation and myofibroblast differentiation, which contributes to the extracellular matrix remodelling of the infarcted myocardium. We recently found that myofibroblasts further differentiate into matrifibrocytes, a newly identified cardiac fibroblast differentiation state. Cardiac fibroblasts of different states have distinct gene expression profiles closely related to their functions. However, the mechanism respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…This subpopulation exhibits strong proliferativity after MI and studies have shown that fibroblasts present in the infarcted scar originate from several other populations, besides resident cells. Recent studies have identified Tcf21 as a resident fibroblast marker [42].…”
Section: Fibroblast Subpopulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This subpopulation exhibits strong proliferativity after MI and studies have shown that fibroblasts present in the infarcted scar originate from several other populations, besides resident cells. Recent studies have identified Tcf21 as a resident fibroblast marker [42].…”
Section: Fibroblast Subpopulationsmentioning
confidence: 99%
“…For example, early myoFBs may not express αSMA but show a stress fiber network and form focal adhesions termed proto-myofibroblasts [48]. Nonetheless, it is generally accepted that αSMA is a marker for myoFBs [42]. Although myoFB is essential for myocardial healing after ischemia, the persistence of myoFB contributes to maladaptive remodeling and progressive decline of cardiac function.…”
Section: Fibroblast Subpopulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, it is unclear if matrifibrocytes are also present in scar tissue from other organs. By combining ATAC-seq and RNA-seq analysis, a recent study indicates that the martrifibrocyte phenotype is maintained by changes in chromatin accessibility and gene expression [ 46 ] and harnessing this cell plasticity may be therapeutically valuable.…”
Section: Mechanical Memorymentioning
confidence: 99%